Nationwide trends of laparoscopic pyloromyotomy in patients with infantile hypertrophic pyloric stenosis in Germany: A slow path forward - Leonhardt, Johannes; Muensterer, Oliver; Alsweed, Ahmad; Schmedding, Andrea (Frontiers in Pediatrics, 2023)
Since the introduction of laparoscopic pyloromyotomy (LP), it has become increasingly popular in many countries. We have noticed an attenuated trend in Germany. The aim of this study was to analyse the distribution of open and LP in Germany. The national database of administrative claims data of the Institute for the Remuneration System in Hospitals (InEK) was analysed regarding numbers of patients with pyloromyotomy in the years 2019-2021. The German quality reports of the hospitals of 2019 and 2020 were analyzed regarding the number of procedures performed per hospital and pediatric surgical department. A total of 2050 patients underwent pyloromyotomy. The incidence of hypertrophic pylorus stenosis (HPS) was 699 and 657 patients in 2019 and 2021, respectively. Regarding age, 31.1% were admitted before 28 days of age. LP gradually increased from 216 patients (30.9%) in 2019 to 239 patients (36.4%) in 2021. Thirty-three laparoscopic operations (4.8%) were converted to an open approach. In 24 of all patients, there was an injury to the stomach, in 20 patients to the duodenum, needing repair with sutures. Analysis of the quality reports indicated that 44% of pediatric surgical departments performed LP. Although LP has been slowly increasing in frequency in Germany recently, about two thirds of patients still undergo an open procedure. Because of decentralized pediatric surgical care in Germany, the individual case load is low, compromising expertise and adaptability.